Combination of Left Ventricular End-Diastolic Diameter and QRS Duration Strongly Predicts Good Response to and Prognosis of Cardiac Resynchronization Therapy. (17th January 2020) - Guo, Zhinian; Liu, Xiaoyan; Cheng, Xiaofeng; Liu, Chuan; Li, Ping; He, Yongming; Rao, Rongsheng; Li, Chun; Chen, Yunlong; Zhang, Yong; Luo, Xiaoyu; Wang, Jiang
Abstract : Background . Approximately 20–40% of recipients of cardiac resynchronization therapy (CRT) do not respond to it based on the current patient selection criteria. The purpose of this study was to identify baseline parameters that can predict CRT response and to evaluate the effect of those predictive parameters on long-term prognosis. Methods . This was a retrospective, nonrandomized, noncontrolled cohort study. Patients who received CRT in our centre were divided into responders and nonresponders by the definition of CRT response (an increase in left ventricular ejection fraction (LVEF) of ≥5% and improvement of ≥1 New York Heart Association (NYHA) class from baseline to the 6-month follow-up). Results . Of the 101 patients, 68 were responders and 33 were nonresponders. Left ventricular end-diastolic diameter (LVEDD; OR: 0.88, 95% CI: 0.81–0.95, P = 0.001 ) and QRS duration (OR: 1.07, 95% CI: 1.04–1.10, P < 0.001 ) were independent predictors of CRT response. The combination of LVEDD and QRS duration was more valuable for predicting CRT response (AUC 0.836; 95% CI: 0.76–0.91; P < 0.001 ). Moreover, the combination of LVEDD ≤ 71 mm and QRS duration ≥ 170 ms had a low incidence of all-cause mortality, HF hospitalisation, and the composite endpoint. In addition, baseline LVEDD had a positive correlation with QRS duration (R = 0.199, P = 0.046 ). Responders to CRT had better LV reverse remodeling. Conclusion . The combination of LVEDD and QRS duration provided more robust prediction of CRT response. Moreover, the combination of LVEDD ≤ 71 mm and QRS duration ≥ 170 ms was associated with a low incidence of all-cause mortality, HF hospitalisation, and the composite endpoint. Our results may be useful to provide individualized patient selection for CRT.